A comprehensive review on the botany, traditional uses, phytochemistry, pharmacology and toxicity of Anagallis arvensis (L).: A wild edible medicinal food plant. (April 2023) - Saleem, Hammad; Khurshid, Umair; Tousif, Muhammad Imran; Anwar, Sirajudheen; Awadh Ali, Nasser A.; Mahomoodally, Mohamad Fawzi; Ahemad, Nafees
Abstract: Medicinal plants, since times immemorial, have been used in virtually all cultures for therapeutic purposes. Anagallis arvensis (L.) is a well-known medicinal plant traditionally utilized for a varied range of disorders including wound healing, lung problems, kidney stones, urinary tract infections, gout, and rheumatic conditions. This review is an attempt to summarize and comprehend the fragmented information until now published in the literature on the biochemical and toxicological perspective of A. arvensis. The literature was searched electronically from PubMed, EMBASE, Scopus, Science Direct, Ovid MEDLINE and Google Scholar. It was found that ethnomedical uses of A. arvensis plant and parts have been recorded throughout the world, where it has been used against a panoply of diseases. Phytochemical search has led to the identification of flavonoids, terpenoids, triterpenoid glycosides, phytosterols as main classes of secondary metabolites with a few other classes. A wide spectrum of in vivo and in vitro pharmacological activities have been reported from fresh plant material and its crude extracts and/or fractions. However there is currently a dearth of structure-activity studies of the isolated compounds and mechanistic studies from this species. The plant has also been reported for in vivo toxicity. It is clear from this review that A. arvensis, though traditionally used by various cultures harbour a plethora of bioactive compounds exhibiting multifarious biological effects that could be exploited as biopharmaceuticals. Nonetheless, additional research work and structure-activity studies arekey prerequisite to transmute the empirical claims on the utilization of A. arvenisis in folklore medicines and a food plant into scientific shreds of evidence. Highlights: Anagallis arvensis (L.) is a well-known wild edible medicinal food plant traditionally utilized for treating common ailments. A systematic literature review of the plant was conducted using different databases. Flavonoids, terpenoids, triterpenoid glycosides, and phytosterols are main classes of phytochemicals. Anagallis arvensis provides therapeutic effects against different health problems and can be further studied as nutraceutical.